2023
DOI: 10.46281/asfbr.v7i1.1916
|View full text |Cite
|
Sign up to set email alerts
|

Customer Satisfaction on E-Banking Services Among University Students in Malaysia

Abstract: Electronic banking (e-banking) has become increasingly important due to its convenience and benefits to banking customers. The purpose of this study is to examine the factors influencing customer satisfaction with e-banking services among university students in Malaysia. Using a standardized questionnaire, the study utilized a cross-sectional design to collect data from 87 students based in Selangor, Malaysia. The findings show that reliability, security, and perceived usefulness are positively associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…However, some business professionals and academicians. Halim et al (2023) argue that customers who display satisfaction can cease to be loyal, hence suggesting that all loyal customers may not be satisfied whereas all satisfied customers do tend to be loyal. This study infers that the impact of CKM is more on customer trust than on customer satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…However, some business professionals and academicians. Halim et al (2023) argue that customers who display satisfaction can cease to be loyal, hence suggesting that all loyal customers may not be satisfied whereas all satisfied customers do tend to be loyal. This study infers that the impact of CKM is more on customer trust than on customer satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Many empirical studies have employed multivariate analysis techniques, such as SERVQUAL or path analysis, frequently utilized in previous marketing research, to investigate the relationship between banking services and customer satisfaction within the banking industry. These studies have consistently demonstrated that enhancing the quality of banking services can positively impact customer satisfaction and have a favorable impact on bank profitability (Boonlertvanich, 2019;Halim et al, 2023;Johnston, 1997;Oppewal & Vriens, 2000;Paul et al, 2016;Teeroovengadum, 2022;Varki & Colgate, 2001). Uddin (2020) demonstrated that the quality of banking services, including exemplary ATM service, mobile banking, and call center quality, is paramount in fostering customer loyalty and enhancing customer satisfaction.…”
Section: Effect Of Service Quality On Customer Satisfactionmentioning
confidence: 98%